جماليات اللون في قصيدة (للعلم الأخير لون البستان) للشاعر كاظم الحجاج - محمد طيب, ريم (Journal of College of Education, 2021)
The sense of beauty and the practice of research in the gaps, and the displacement of the poetic text through the intake and tension, which works to provoke the aesthetic response by the recipient, which is the main objective of the aesthetic studies Fasida (for the last science color orchard), which we are based on the expression of aesthetic fusion between the aesthetic color Its ability to form an aesthetic shift works to add aesthetic dimensions Each color refers to a sentimental or emotional dimension that reflects the historical and social depth, which concerns each color of the flag of Iraq, the poet tried to lay of these aesthetic dimensions of color, which he described as an orchard or garden gathering everything that is T History or social and beautiful in the memory of the poet.
Keywords: Beauty, aesthetics, color, science, garden.